Analysis of Irony in WS. Rendra's Poem Sebatang Lisong: A Stylistic Study - lailatus syifa, Lailatus Syifa; Rahman, Bohri (Educational Insights, 2025)
This article aims to describe the majas satire according to its type in the poem entitled Sajak Sebatang Lisong by WS. Rendra. This article uses descriptive qualitative research methods with reading and note-taking techniques. The results of this article are 21 data that show the majas sindiran, namely 3 majas cynisme, 7 majas sarcasm, 5 majas irony, 3 majas satire, and 3 majas innuendo. Thus, the most dominating sarcasm in the poem entitled Sajak Sebatang Lisong by WS. Rendra is sarcasm. In the world of education, especially literary education, style is important in shaping distinctive characteristics, character, ethics, and critical thinking. Style distinguishes one writer from another. Therefore, language style plays a role in the world of education, just as language plays a crucial role in various fields, including education, politics, society, and economics. Through language style, particularly satirical figures of speech, one can reveal a person's character and ethics in satire. A person may satirize subtly or directly. This reveals a person's character and ethics, which are reflected through the language style they use. In addition, style can train critical thinking through the language it uses. Poetry, for example, requires critical thinking to understand its meaning because of its dense use of language.